Analysis of morbidity and mortality of cervical cancer in Zabaikalskii krai - Tatyana V. Bogomazova; Tatyana N. Chimitdorzhieva (IP Berlin A.V., 2020)
Relevance. Currently, noncommunicable diseases are responsible for the majority of deaths worldwide. Cervical cancer (СС) is actual medical and social problem. Comparative analysis of morbidity, mortality and state of oncological care in Zabaikalskii krai and Russian Federation was purpose of this study. Aim. Estimation of morbidity and mortality from cervical cancer in the Zabaikalskii krai in dynamics over 10 years. Materials and methods. The assessment was carried out on the basis of an analysis of statistical data concerning the burden of morbidity and mortality from cancer in the territory of the Zabaikalskii krai and the Russian Federation. Statistical analysis was performed using the Statistica 10 software. Standardized indicators were used to analyze morbidity and mortality. Differences were considered statistically significant at an error level of p0.05. Results. Analysis cervical cancer incidence of the Zabaikalskii krai and the Russian Federation in dynamics from 20072017 (100 000 female population) demonstrates a significant increase in the incidence of cervical cancer. On the territory of the Russian Federation, there is a steady increase on average by 2.26% annually, the growth dynamics over this period amounted to 25.81%, and in 2017 amounted to 15.76. In the Zabaikalskii krai in 2017, the incidence of cervical cancer was 41.54. In dynamics over the past 10 years, this indicator increased by 46.42%, which is significantly higher than in the Russian Federation (p0.01). The analysis of standardized indicators of mortality from cervical cancer in the structure of mortality from cancer in Russia in 2017 amounted to 5.18%, which corresponds to 10th place. Mortality in the first year since diagnosis was 14.6%. In the group of women of reproductive age 3039 years, mortality from cervical cancer was also maximum (23.6%) compared with other age groups. Mortality from cervical cancer in the Zabaikalskii krai was 7.17 in 2017. This indicator is higher than the all-Russian values by 38.41% (p0.01). In dynamics over 10 years, a decrease in mortality in the Zabaikalskii krai by 6.39% is noted. Conclusion. It should be noted that a significant increase in the incidence of cervical cancer, and a decrease in mortality from this pathology, may indicate some success in the diagnosis and treatment of this pathology. In this regard, the search for new diagnostic, prognostic and predictive markers at this stage is relevant in solving this all-Russian medical and social problem.